The Epidermis in Microgravity and Unloading Conditions and Their Effects on Wound Healing - Bacci, Stefano; Bani, Daniele (Frontiers in Bioengineering and Biotechnology, 2022)
The future objectives of human space flight are changing from low-term permanence in the International Space Station to missions beyond low Earth orbit to explore other planets. This implies that astronauts would remain exposed for long time to a micro-gravity environment with limited medical support available. This has sparkled medical research to investigate how tissues may adapt to such conditions and how wound repair may be influenced. This mini-review is focused on the effects of microgravity and unloading conditions on the epidermis and its keratinocytes. Previous studies, originally aimed at improving the in vitro protocols to generate skin substitutes for plastic surgery purposes, showed that epidermal stem cells cultured in simulated microgravity underwent enhanced proliferation and viability and reduced terminal differentiation than under normal gravity. In the meantime, microgravity also triggered epithelial-mesenchymal transition of keratinocytes, promoting a migratory behavior. The molecular mechanisms, only partially understood, involve mechano-trasduction signals and pathways whereby specific target genes are activated, i.e., those presiding to circadian rhythms, migration, and immune suppression, or inhibited, i.e., those involved in stress responses. However, despite the above in vitro studies suggest that microgravity would accelerate keratinocyte growth rate and migration, in vivo findings on animals in experimental set-ups to simulate low gravity rather suggest that prolonged mechanical unloading contributes to delayed and impaired epidermal repair. This is in keeping with the finding that microgravity interferes at multiple levels with the regulatory signals which coordinate the different cell types involved in the repair process, thereby negatively influencing skin wound healing.